Assessing Gender Equality in Educational Opportunities: A Study of Female Online Motorcycle Taxi Drivers in Malang City - Muayyad, Muhamad Shobichul; Wiyono, Dwi Fitri (Abjadia : International Journal of Education, 2023)
This study explores the fundamental aspects, issues, objectives, methodology, findings, recommendations, and suggestions related to gender equality in educational opportunities for female online motorcycle taxi drivers in Malang City. The emergence of women in this profession has seen a substantial increase since 2016, coinciding with the growth of online transportation services. Utilizing a case study approach, the research reveals that the rationale behind women choosing this profession extends beyond economic considerations to encompass social dynamics and a shift in gender roles. The findings emphasize the need for jobs that go beyond economic requirements, highlighting the evolving roles of women in society. The study suggests that policymakers focus on labor laws, especially those aligned with the challenges posed by the fourth industrial revolution. The recommendations aim to address the complexities surrounding gender equality in educational and employment opportunities for female online motorcycle taxi drivers.